2011
DOI: 10.1111/j.1365-2869.2010.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of insomnia among Chinese adults in Hong Kong: a population‐based study

Abstract: Summary Prevalence estimates of insomnia in western general populations are well documented, but population‐based epidemiological data on insomnia in Chinese adults are scarce. The aims of the present study were to determine the prevalence of insomnia in the general population of Hong Kong, compare components of sleep disturbances and lifestyle factors stratified by sex, and identify risk factors for insomnia. Using a population‐based cross‐sectional design, a total of 5001 Chinese adults aged ≥18 years comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
131
9
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(172 citation statements)
references
References 53 publications
29
131
9
3
Order By: Relevance
“…The mean age in the present study sample was 57.8 years (SD=11.6), lower than that in the studies used for comparison, which might explain the difference observed, as general population studies show that sleep problems are more frequent as age advances (17)(18) . In a study of 5001 adults from the general population, the proportion of "bad sleepers" corresponded to 39.4% (19) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age in the present study sample was 57.8 years (SD=11.6), lower than that in the studies used for comparison, which might explain the difference observed, as general population studies show that sleep problems are more frequent as age advances (17)(18) . In a study of 5001 adults from the general population, the proportion of "bad sleepers" corresponded to 39.4% (19) .…”
Section: Discussionmentioning
confidence: 99%
“…In a general population study (N=5,001), 9.4% of participants reported being unable to fall asleep within 30 minutes (19) .…”
Section: Discussionmentioning
confidence: 99%
“…4 In Hong Kong, 39.4% of the adult population (equivalent to 2.2 million) are affected by insomnia. 5 It is recognized that, left untreated, transient insomnia can evolve to a chronic condition. [1][2][3] Indeed, individuals reporting disturbed sleep are more likely to report recurrent health problems and emotional distress.…”
Section: Introductionmentioning
confidence: 99%
“…국내외적으로 성인의 수면장애 유병률은 13.14~39.4%로 (Choi, Kim, & Kim, 2013;Wong & Fielding, 2011) 수면과 관련이 있는 변수 및 영향요인으로 일반적 특성에서 연령, 결혼상태, 취업여부 (Eun & Cha, 2010), 교대근무, 월 수입 (Kim, Kim, & Kim, 2006), 음주 (Wong & Fielding, 2011), 질병, 복용약물, 직업유무, 규칙적 운동유무 및 운동 시간 (Choi et al, 2013), 신체적 측면에서 전립선 증상을 포 함한 하부요로증상 (Shin, Kang, & Shin, 2008), 밤에 소변 본 횟수 (Choi et al, 2013), 지각된 건강상태 (Wong & Fielding, 2011), 정신 심리적 측면에서 삶의 질 (Gureje, Kola, Ademola, & Olley, 2009), 생활패턴 측면에서 일주기리듬 (Kim, Lee, Kim, Jang, & Duffy, 2012) 등으로 나타났다.…”
unclassified
“…성인남성이 포함된 수면 관련 선행연구들을 살펴보면, 성 인남성의 불면증의 유병률 조사 (Wong & Fielding, 2011), 남성정규직 소방공무원의 수면영향분석 , 45세 이상 성인의 수면문제 발생률과 위험요인 (Choi et al, 2013), 성인남녀의 활동시간과 총수면시간의 차이에 따른 관 련요인분석 (Eun & Cha, 2010), 남성노인 대상의 수면의 질 (Shin et al, 2008) (Table 1). …”
unclassified